Using Living Germplasm Collections to Characterize, Improve, and Conserve Woody Perennials. Issue 6 (1st November 2019) - Migicovsky, Zoë; Warschefsky, Emily; Klein, Laura L.; Miller, Allison J.
ABSTRACT: Woody perennial plants make up nearly half of plant diversity and represent one‐third of the world's major crop species, yet effective strategies to maintain and preserve these important species require additional attention. The majority of conservation programs focus on seed storage; however, seeds of many woody perennial plants are difficult to maintain in seed banks because they are recalcitrant. In addition, most woody perennial crops are clonally propagated, and seed‐based conservation efforts miss clonal lineages that form the foundation of woody perennial agriculture. Woody crops are often best maintained as living collections, but these compose only 5.8% of ex situ germplasm collections. Living germplasm collections are critical resources for exploring and conserving genetic and phenotypic diversity and provide novel material for breeding efforts. In this review, we examine how living germplasm collections can be used for for phenotypic description, genetic characterization, and plant breeding. Lastly, we outline the importance of conserving these valuable resources and highlight the need for conservation strategies that are appropriately designed for woody perennial species.